Unusual Maths clock or Reverse Traveling Salesman Problem - Valerij F. Ochkov; Elena P. Bogomolova (Открытое образование (Москва))
The article discusses some of the mathematical problem, attached to the clock. We show how to use the clock in the classroom for mathematics to illustrate some mathematical problems